The Relationship Between Financial Management, Marketing, and Human Resources with the Competitiveness Of MSME - Fidyah Arini Kusuma Wardhani; Supriyadi; Devi Maya Sofa; Rizki Ramadhani; Kusman Paluala (CV. Get Press Indonesia, 2025)
Increasingly fierce competition in Pasar Raya Padang poses significant challenges for Micro, Small, and Medium Enterprises (MSME) in maintaining their market position. Many MSME face obstacles related to financial management, marketing strategies, and Human Resource (HR) management, which can hinder business growth and long-term sustainability. This study aims to analyze the relationship between financial management, marketing, and human resources with the competitiveness of MSME in Pasar Raya Padang. The research employed a quantitative method with a survey approach involving 50 purposively selected MSME owners. Data were analyzed using the Chi-Square test to determine the significance of the relationship among variables. The results showed that financial management, marketing, and HR have a significant relationship with MSME competitiveness. The Chi-Square test revealed p-values of 0.002 for financial management, 0.010 for marketing, and 0.030 for HR, all below 0.05, indicating statistically significant effects. MSME with better financial management, more planned marketing strategies, and more effective HR practices tend to demonstrate higher competitiveness. In conclusion, strengthening financial management, marketing, and HR is crucial for enhancing MSME competitiveness in Pasar Raya Padang. The study implies the importance of providing intensive training and mentoring programs to support MSME capacity building.